2017
DOI: 10.2340/16501977-2190
|View full text |Cite
|
Sign up to set email alerts
|

Long-term mental fatigue after traumatic brain injury and impact on employment status

Abstract: Objective: Long-term mental fatigue following traumatic brain injury is endorsed as one of the most distressing symptoms, interfering considerably with return to work and social life. The objective of this cross-sectional study was to estimate the prevalence of long-term mental fatigue after traumatic brain injury and to evaluate its association with employment status. Methods: All patients (age range 19-65 years) diagnosed with traumatic brain injury irrespective of severity at Kungälv Hospital, Kungälv, Swed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 32 publications
5
43
0
1
Order By: Relevance
“…Moreover, only mental fatigue was significantly related to unfavorable long-term functional outcome after SAH, compared to physical fatigue and mood problems. In this study, mental fatigue was identified as an important factor post-SAH, in line with previous studies defining mental fatigue as most distinctive for brain injury [9,10]. Despite some overlap, our data support a distinction between mental and physical fatigue.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, only mental fatigue was significantly related to unfavorable long-term functional outcome after SAH, compared to physical fatigue and mood problems. In this study, mental fatigue was identified as an important factor post-SAH, in line with previous studies defining mental fatigue as most distinctive for brain injury [9,10]. Despite some overlap, our data support a distinction between mental and physical fatigue.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, mental fatigue was identified as an important factor post‐SAH, in line with previous studies defining mental fatigue as most distinctive for brain injury . Despite some overlap, our data support a distinction between mental and physical fatigue.…”
Section: Discussionsupporting
confidence: 91%
“…Family and social life can also be affected, as the symptoms can be triggered in any situation requiring even small amounts of mental and/or physical effort. On the socioeconomic level, PCS is related to prolonged sick leave and unemployment [12] [13].…”
Section: Introductionmentioning
confidence: 99%
“…F atigue is common in the early phase of recovery after stroke (reported by 23-75% of people) (1) and continues to affect daily life in the chronic phase after stroke (termed "post-stroke fatigue"; PSF). PSF affects the individual's everyday life (2), functioning, and can negatively interfere with rehabilitation (1,3). However, there is insufficient evidence regarding the efficacy of any non-pharmacological intervention for PSF (4)(5)(6)(7).…”
mentioning
confidence: 99%